2008
DOI: 10.1590/s0004-27302008000800003
|View full text |Cite
|
Sign up to set email alerts
|

HRPT2-related familial isolated hyperparathyroidism: could molecular studies direct the surgical approach?

Abstract: It is still debatable which is the best management to familial forms of hyperparathyroidism. Conservative, minimally invasive or aggressive surgical approaches have been proposed from different groups around the world. Our objective was to study the gene mutation, expression of HRPT2 and the clinical outcome after 32 years of follow-up in one Brazilian kindred with familial isolated hyperparathyroidism (FIHP). Clinical and biochemical data, direct sequencing of the HRPT2 gene, analysis of parafi bromin express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…It is notable that the three families with FIHP in the present study all carried mutations of the CDC73 gene. The same genetic background of FIHP and HPT‐JT supports the theory that a subset of patients with FIHP is a variant of HPT‐JT with incomplete penetrance . In previous studies, FIHP is associated with a high frequency of MEN1 mutations ranging between 22% and 57% .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…It is notable that the three families with FIHP in the present study all carried mutations of the CDC73 gene. The same genetic background of FIHP and HPT‐JT supports the theory that a subset of patients with FIHP is a variant of HPT‐JT with incomplete penetrance . In previous studies, FIHP is associated with a high frequency of MEN1 mutations ranging between 22% and 57% .…”
Section: Discussionsupporting
confidence: 65%
“…The same genetic background of FIHP and HPT-JT supports the theory that a subset of patients with FIHP is a variant of HPT-JT with incomplete penetrance. 4,7,23,24 In previous studies, FIHP is associated with a high frequency of MEN1 mutations ranging between 22% and 57%. 8,25,26 However, MEN1 gene mutation has not been detected in our FIHP families.…”
Section: Discussionmentioning
confidence: 92%
“…Patients with confirmed HPT-JT syndrome have a very high risk of recurrence in the same or other glands, which is at least 25%, but which may occur in the majority of patients at follow-up extending to 30 years 6,8,9,38,4043. Therefore, the diagnosis of parafibromin-deficient (HPT-JT type) parathyroid tumors should precipitate long-term follow-up for the possibility of late recurrence or metachronous disease, whether or not WHO criteria for malignancy are met.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Silveira and colleagues showed a high rate of recurrence (4/9) and/or persistent (2/9) PHPT. The authors speculated that aggressive treatment may be warranted and genotype-phenotype data may be able to direct the surgeon (18). The recurrence rate of PHPT in this cohort was 25.0%.…”
Section: Discussionmentioning
confidence: 99%